Let \( f(x) = \frac{a x + b}{c x + d} \).
To differentiate \( f(x) \), we apply the quotient rule, which states that if \( f(x) = \frac{u(x)}{v(x)} \), then
\[ f'(x) = \frac{u'(x)v(x) - u(x)v'(x)}{(v(x))^2} \]
where \( u(x) = a x + b \) and \( v(x) = c x + d \).
Calculate the derivatives:
Substituting into the quotient rule gives:
\[ f'(x) = \frac{a(c x + d) - (a x + b)c}{(c x + d)^2} \]
Simplifying the numerator:
\[ f'(x) = \frac{a(c x + d) - c(a x + b)}{(c x + d)^2} \]
This results in:
\[ f'(x) = \frac{a(c x + d) - c(a x + b)}{(c x + d)^2} = \frac{a}{c x + d} - \frac{c(a x + b)}{(c x + d)^2} \]
\(\boxed{f'(x) = \frac{ad - bc}{(cx + d)^2}}\)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.